Postmodern Theory and Its Two Major Self-Deceptions - Muhic, Ferid (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2014)
Postmodern Theory and Its Two Major Self-Deceptions